Children during the Holocaust - Heberer, Patricia Mitwirkender; United States Holocaust Memorial Museum (Documenting life and destruction, 2011)
Children during the Holocaust, from the United States Holocaust Memorial Museum's Center for Advanced Holocaust Studies, tells the story of the Holocaust through the eyes, and fates, of its youngest victims. The ten chapters follow the arc of the persecutory policies of the Nazis and their sympathizers and the impact these measures had on Jewish children and adolescents-from the years leading to the war, to the roundups, deportations, and emigrations, to hidden life and death in the ghettos and concentration camps, and to liberation and coping in the wake of war. This volume examines the reactions of children to discrimination, the loss of livelihood in Jewish homes, and the public humiliation at the hands of fellow citizens and explores the ways in which children's experiences paralleled and diverged from their adult counterparts.